2011
DOI: 10.1523/jneurosci.5092-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Progressive Nigral Neurodegeneration Induced by the Parkinson's Disease-Associated G2019S Mutation in LRRK2

Abstract: The G2019S mutation in the leucine-rich repeat kinase 2 (LRRK2) gene is the most common genetic cause of Parkinson's disease (PD), accounting for a significant proportion of both autosomal dominant familial and sporadic PD cases. Our aim in the present study is to generate a mammalian model of mutant G2019S LRRK2 pathogenesis, which reproduces the robust nigral neurodegeneration characteristic of PD. We developed adenoviral vectors to drive neuron-specific expression of full-length wild-type or mutant G2019S h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 21 publications
6
129
1
Order By: Relevance
“…Injection of adenoviruses expressing human G2019S but not wild-type LRRK2 to the striatum of adult rats induces hyperphosphorylation of tau and progressive DA neuron loss [123]. In mice, herpes simplex virus amplicon vectors expressing human G2019S LRRK2 caused degeneration of DA neurons, which was attenuated by pharmacological inhibition of LRRK2 kinase activity [113].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…Injection of adenoviruses expressing human G2019S but not wild-type LRRK2 to the striatum of adult rats induces hyperphosphorylation of tau and progressive DA neuron loss [123]. In mice, herpes simplex virus amplicon vectors expressing human G2019S LRRK2 caused degeneration of DA neurons, which was attenuated by pharmacological inhibition of LRRK2 kinase activity [113].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…This expression pattern is in contrast to LRRK2 expression observed in the postmortem brain of LRRK2-linked PD patients. 66 Further, in these animal models, it was found that LRRK2 expression diminished over time, 32,65 which is unlikely to occur in humans. However, a key advantage of such studies is the ability to test and compare multiple mutations and WT controls, where it is much simpler to create an additional test vector, rather than an additional transgenic rodent line.…”
Section: Rodent Modelsmentioning
confidence: 95%
“…65 Further, LRRK2 expression was shown to diminish over time. In contrast, BAC transgenic mice studies have reported 5-10 times increased LRRK2 expression in comparison to endogenous levels.…”
Section: Rodent Modelsmentioning
confidence: 99%
“…This model is the first model that directly implicates kinase activity being responsible for toxicity in vivo in a mammalian model, supported by the lack of effect in the kinase dead model, as well as attenuation of the neuronal loss by kinase inhibitors GW5074 and indirubin-3′-monooxime. The second viral model, the only published rat model to date, used a second generation adeno-viral serotype 5 vector, with transgene expression driven by the neuronal-specific human synapsin-1 promoter to express human WT and G2019S LRRK2 in rat brain (Dusonchet et al, 2011). Injections were delivered to the striatum and retrograde expression in the nigra was around 2 fold expression level overall, although with only 30% of all neurons transduced, this suggested very high levels in individual neurons.…”
Section: Over-expression Of Lrrk2mentioning
confidence: 99%